Sardine Fish Oil By Sentrifugation and Adsorbent for Emulsion - Kristina Haryati; Sugeng Heri Suseno; Nurjanah Nurjanah (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Sardine fish meal by-product contain eicosapentaenoic acid (EPA) and docosahexaenoic (DHA) and it can be made as emulsion. The purpose of this study were to determine the best fish oil emulsion by mixingthe oil phase (lecithin 3% and oil) and water phase (carboxymethyl cellulose/CMC 2% and fruit juice) and then stored until creaming, and the emulsion is analyzed their viscosity, pH, percent of stability and longseparation. Sardine oil is separated from the emulsion and tested oxidation parameters. The best emulsion was fish oil emulsion after refined without citric acid (RTS) with viscosity (2470.31 cP), pH (5.64), percent of stability (56.14%) and long separation (14 days). Primary and secondary oxidation parameters of RTS  were FFA (14.87%), PV (14.43 meq/kg), AV (32.57 meq KOH/g), AnV (17.3 meq/kg), and Totox (46.16 meq/kg).